2019
DOI: 10.1021/acs.iecr.9b00556
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Investigations of Double Emulsion Preparation by Ultrasonication

Abstract: Double emulsion preparation by ultrasonication is investigated in order to optimize the outer droplet size and the encapsulation efficiency. The effects of the sonication time, the oil viscosity, and the fractions of salt and primary emulsion are studied. A correlation is developed in order to predict the mean droplet diameter as a function of these parameters. The model is valid in the dissipation energy subrange. It accounts for the effects of salt within the surface force group, the oil viscosity within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 74 publications
1
29
0
2
Order By: Relevance
“…It is also shown that the oil phase can contain one and/or multiple water droplets depending on the emulsion type. These results agree well with the literature, showing the formation of multiple emulsions using microscopy techniques [23,24]. We note that the higher stability at the higher concentration (50 wt%) of primary emulsion can be associated with increased solution viscosity due the larger volume fraction of dispersed phase [17].…”
Section: Effect Of Primary Emulsion Concentration On the Formation Ansupporting
confidence: 92%
“…It is also shown that the oil phase can contain one and/or multiple water droplets depending on the emulsion type. These results agree well with the literature, showing the formation of multiple emulsions using microscopy techniques [23,24]. We note that the higher stability at the higher concentration (50 wt%) of primary emulsion can be associated with increased solution viscosity due the larger volume fraction of dispersed phase [17].…”
Section: Effect Of Primary Emulsion Concentration On the Formation Ansupporting
confidence: 92%
“…Under suitable homogenization conditions, the final droplet size depends strongly on the characteristics of the oil and emulsifier used [ 34 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. In general, small droplet sizes can be obtained more effectively by low-energy approaches than by high-energy approaches, but the former are more limited in the types of oils and emulsifiers that can be used [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between coalescence and diffusion are described in literature for several formulations: when the inner water droplets coalesce, and thus increase their size, release is increased as well [21]. Khadem et al [22] reported the spontaneous breakdown of the double emulsion structure after a certain degree of osmotic swelling of the inner water droplets. These examples illustrate that the initial instability mechanism can be different from the observed result.…”
Section: Interaction Of Instabilitiesmentioning
confidence: 99%